Peran Ustadzah Thaharah Dalam Pembelajaran Toilet Training Untuk Menerapkan Perilaku Hidup Bersih dan Sehat Pada Anak Kelompok A di RA Perwanida Ketintang - Sidiq, Adelia Miranti; Umairi, Mushab Al; Maghfiroh, Lailatul (Journal of Childhood Education, Development and Parenting, 2024)
Researchers discovered an activity that is rarely found in other TK/RA institutions. This activity is Toilet Training learning which is supported by the role of an educator with the term "Ustadzah Thaharah" so that through this activity students at RA institutions can get used to maintaining personal hygiene and the surrounding environment. This research aims to describe the role of ustadzah thaharah in toilet training lessons to familiarize students with maintaining cleanliness at KB-RA Perwanida Ketintang Surabaya. Apart from that, the researcher wants to describe the impact of toilet training learning on group A students at KB-RA Perwanida Ketintang Surabaya. This research uses descriptive qualitative methods. The research subjects consisted of ustadzah thaharah, and several group A students at RA Perwanida Ketintang Surabaya. Data collection in this research used interview, observation and documentation techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Through learning about toilet training, group A children can implement clean and healthy living habits as well as cleanliness of the surrounding environment. Educate students about toilet etiquette, train students' ability to urinate, and teach students to get used to keeping themselves and their surroundings clean. And students are able to resolve the urge to defecate independently, and are able to implement clean and healthy living behavior and cleanliness of the surrounding environment.